Faktor Yang Mempengaruhi Kebijakan Dividen Pada Perusahaan Manufaktur Yang Terdaftar di Bursa Efek Indonesia - Indah Septiana; Nurdiawansyah Nurdiawansyah; Aminah Aminah; Luke Suciyati Amna; Herry Goenawan Soedarsa (Universitas Bandar Lampung (UBL), 2020)
Dividend policy is a decision whether profits generated by a company will be distributed to shareholders as dividends or made retained earnings.The purpose of this study was to determine the factor that affect the dividend policy in the manufacture company listed in indonesia stock exchange. The population in this study is a 139 mining companies open in the Indonesia Stock Exchange (BEI). The sample selection uses a purposive sampling method in order obtain a sample of 23 companies. The analysis techique used is multiple linear regression, analysis technique used is multiple linear regression, analysis using SPSS version 20. The results of this study profitability proxied by Return On Assets has a positive and significant to Dividen Payout Ratio, Liquidity is proxied by Current Ratio negative and no significant to Dividen Payout Ratio, and Firm Size has a positive and significant to Dividend Payout Ratio